2013
DOI: 10.1016/j.aap.2013.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Stability of physical assessment of older drivers over 1 year

Abstract: Older adults represent the fastest-growing population of drivers with a valid driver's licence.Also common in this age group are multiple chronic medical conditions that may have an effect on physical function and driving ability. Determining the reliability of physical measures used to assess older drivers' functional ability is important to identifying those who are safe to continue driving. Most previous reliability studies of clinical physical measures of health used test-retest intervals shorter than thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…The RPW is included in the Assessment of Driving-Related Skills (ADReS), which is a test battery that consists of vision, cognition, and motor/somatosensory function measures that assess skills necessary for safe driving (Carr et al 2010). A study on the stability of physical assessment measures found that the RPW had a moderate relative reliability and low coefficients of variability (CV) values (Smith et al 2013). …”
Section: Methodsmentioning
confidence: 99%
“…The RPW is included in the Assessment of Driving-Related Skills (ADReS), which is a test battery that consists of vision, cognition, and motor/somatosensory function measures that assess skills necessary for safe driving (Carr et al 2010). A study on the stability of physical assessment measures found that the RPW had a moderate relative reliability and low coefficients of variability (CV) values (Smith et al 2013). …”
Section: Methodsmentioning
confidence: 99%
“…Fourteen drivers that demonstrated stable general, physical and cognitive health over their first year in the Candrive study [135], from the Ottawa region and that did not share their vehicle were chosen for detailed analysis. Stable general, cognitive, and physical health allows for analysis while controlling for any influence on their driving behaviours caused by changing health.…”
Section: Driver Behaviour Attributes -Month To Month Trendsmentioning
confidence: 99%
“…Previous analysis has identified a number of measures of specific driver behaviours including choice of road, trip length and trip duration [18]. A focused study of acceleration [19] for drivers with stable general, physical and cognitive health [20] that are sole drivers of their vehicles showed drivers have differing acceleration and deceleration behaviors [1,21,22]. This paper explores the trip level calculated features individually and in combination for their ability to allow two different drivers to be distinguished.…”
Section: Problem Statementmentioning
confidence: 99%